Internal parasitic burdens in brown rats (Rattus norvegicus) from Grenada, West Indies - C. Coomansingh-Springer; V. Vishakha; A. Montanez Acuna; E. Armstrong; R.N. Sharma (Heliyon, 2019)
This study identified the endoparasites in Brown rat (Rattus norvegicus) during May to July 2017 in Grenada, West Indies. A total of 162 rats, 76 females and 86 males were trapped from St. George and St. David parishes in Grenada. The collected fecal samples were examined for parasitic eggs and/or oocysts using simple fecal flotation technique. Adult parasites found in the intestinal tract were examined for identification. The overall prevalence of intestinal parasites among rats was 79 %.Ten helminth species were recovered, several of which were reported for the first time in rodents in Grenada. The internal parasites consist of seven nematodes (Angiostrongylus spp., Nippostrongylus braziliensis, Heterakis spumosa, Strongyloides ratti, Aspiculuris tetraptera, Syphacia spp. and Protospirura spp.), one cestode (Hymenolepsis diminuta), one acanthocephalan (Moniliformis moniliformis) and one protozoa species (Eimeria spp.). The most prevalent zoonotic species were Angiostrongylus spp. (35.2%), Hymenolepsis diminuta (7.4%) and Moniliformis moniliformis (3.1%). Several nonzoonotic endoparasites; which included Nippostrongylus braziliensis (50.6%), Heterakis spumosa (15.4%), Strongyloides ratti (43.2%), Aspiculuris tetraptera (2.5%), Syphacia spp. (1.9%), Protospirura spp. (1.2%) and Eimeria spp. (4.7%) were also identified. The most prevalent parasites were Nippostrongylus brasiliensis (50.6%), Strongyloides ratti (43.2%) and Angiostrongylus spp. (35.2%). Co-infections occurred with up to six species per rat showing different combinations of parasitic infections.